After the Dinosaurs : The Age of Mammals - Prothero, Donald R. (Book collections on Project MUSE., 2006)
A fascinating study of the thousands of new animal species that walked in the footsteps of the dinosaurs-and the climate changes that brought them forth. The fascinating group of animals called dinosaurs became extinct some 65 million years ago (except for their feathered descendants). In their place evolved an enormous variety of land creatures, especially mammals, which in their way were every bit as remarkable as their Mesozoic cousins. The Age of Mammals, the Cenozoic Era, has never had its Jurassic Park, but it was an amazing time in earth's history, populated by a wonderful assortment of bizarre animals. The rapid evolution of thousands of species of mammals brought forth many incredible creatures'including our own ancestors. Their story is part of a larger story of new life emerging from the greenhouse conditions of the Mesozoic, warming up dramatically about 55 million years ago, and then cooling rapidly so that 33 million years ago the glacial ice returned. The earth's vegetation went through equally dramatic changes, from tropical jungles in Montana and forests at the poles. Life in the sea underwent striking evolution reflecting global climate change, including the emergence of such creatures as giant sharks, seals, sea lions, dolphins, and whales. Engaging and insightful, After the Dinosaurs is a book for everyone who has an abiding fascination with the remarkable life of the past.